Acoustic community signature of the seagrass bed in Calero, Liloan Cebu, Philippines - Villarubia, Mariel Rose A. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2020)
The seagrass bed is an ecologically important ecosystem that is widely affected by coastal developments. This study aimed to characterize the acoustic pattern of the seagrass bed in Marina Fish Sanctuary, Liloan and provide information on possible factors that affect the sound propagation in the seagrass bed in terms of the seagrass cover. Acoustic survey through long term passive acoustic monitoring and visual survey were conducted. Most of the months were characterized by high frequency sounds (≥ 40 kHz), except in September, which was characterized by low frequency sounds (<20 kHz). High intensity sounds were prominent from August to November 2019, but not in the last three months of sampling. The acoustic signature of the seagrass habitat exhibited seasonal, diurnal, and tidal patterns. The lunar cycle was found to have no influence on the production of biological sounds in the seagrass bed. Marina bay is abundant of seagrass species, with Thalassia hemprichii dominating the site. Only few of the species thrived in the deep part, which was also characterized by a muddy substrate. The abundance of seagrass species accounted for the seven invertebrate families identified, with Holothuriidae being the dominant family. Seagrasses produce oxygen bubbles during photosynthesis that can attenuate high frequency acoustic signals. Thus, soundscape ecology and long term passive acoustic monitoring can give information on the acoustic biological activities of marine organisms, and can be used to assess the health of the seagrass ecosystem and improve conservation practices.